Diversity of Phytophagous and Entomophagous Insect on Yellow Alder Flower (Turnera subulata J.E SM and Turnera ulmifolia L.) Around the Palm Oil (Elaeis guineensis J.) Plantations - Ryan Hidayat; Chandra Irsan; Arum Setiawan (Science and Technology Indonesia, 2018)
Yellow alder flower, with Indonesian name bunga pukul delapan, can influence the existence of phytophagous and entomophagous insect around any crops. The existence of these phytophagous and entomophagous insects would affect the diversity of predator and parasitoid insect species that come to these crops. This research was aimed to study the role of yellow alder flower in their influence of the presence of predatory and parasitoid insect that active in the Turnera subulata dan Turnera ulmifolia. The research was conducted at July to August 2017 in palm oil plantation of PT. Tania Selatan branch Burnai Timur 1. The results showed that phytophagous insect found in the yellow alder flower belonging to 6 orders and 25 families. Meanwhile for the entomophagous insect, it was belonging to the 7 orders and 15 families. The diversity index in Turnera subulate and Turnera ulmifolia was in range of 0.063 and 2.912 or higher than 2. The dominant index was low (in range of 0.091 to 0.125) and the evenness index was high enough in range 0.738 – 0.752.